NIR Light Driven Terahertz Wave Modulator with a Large Modulation Depth Based on a Silicon‐PEDOT:PSS‐Perovskite Hybrid System. Issue 4 (29th January 2020) - Lai, Weien; Ge, Chengda; Yuan, Hao; Dong, Qingfeng; Yang, Deren; Fang, Yanjun
Abstract: Terahertz (THz) all‐optical modulation, that is, the transformation from optical signal to THz signal, is critical for the THz communication system. Here, an ultrasensitive all‐optical modulator for THz waves based on a silicon‐poly(3, 4‐ethylenedioxythiophene)/poly(styrene sulfonate) (PEDOT:PSS)‐perovskite hybrid system is presented, with the silicon substrate as the photon absorption layer, which enables its near‐infrared (NIR) light driven THz modulation and exhibits a large modulation depth up to −45 dB under a moderate light intensity of 2.18 W cm −2 . The enhanced modulation mechanism of the hybrid system is investigated, which demonstrates the essential role of PEDOT:PSS and passivated perovskite layers in promoting the charge separation at the interface and therefore increasing the surface photoconductivity of the device under light irradiation. This study opens a new window for the design and preparation of high‐performance THz photonic devices. Abstract : A near‐infrared (NIR) light driven THz modulator based on a silicon‐PEDOT:PSS‐perovskite hybrid system is experimentally demonstrated, which can sensitively respond to the NIR light excitation with a large modulation depth up to −45 dB. This outstanding THz modulation capability, together with the NIR light driven feature, offers great potential to improve the overall performance of THz communication systems.